Predictability of retroperitoneal lymph node metastasis by using clinicopathologic variables in surgically staged endometrial cancer. Issue 3 (1st April 2006) - Taskiran, C.; Yuce, K.; Geyik, P. O.; Kucukali, T.; Ayhan, A.
Abstract : The purpose of this study was to predict lymphatic involvement in endometrial cancer using clinicopathologic variables of patients treated with surgical staging. Overall, 461 patients treated with an initial surgical staging procedure including complete pelvic–para-aortic lymphadenectomy were included. The mean number of resected lymph nodes was 27 (median 26; range 15–83), and 54 patients (12%) had lymphatic involvement. Of these patients, 32 had only pelvic, 15 had both pelvic and para-aortic, and 7 had isolated para-aortic metastases. In the multivariate analysis, deep myometrial invasion ( P = 0.02), lymphvascular space invasion ( P = 0.001), positive peritoneal cytology ( P = 0.002), and cervical involvement ( P = 0.003) predicted retroperitoneal lymph node metastasis (RLN) significantly. Two hundred seventy-four patients (59.4%) had at least one of these poor prognostic factors identified by multivariate analysis. In this patient population, 53 (19.3%) had lymphatic involvement compared to 1 patient in the group of 187 patients with low-risk criteria. Ninety-eight percent of patients with RLN were predicted by this model, and with the advent of accurate diagnostic techniques, 40% of patients could be saved from undergoing lymphadenectomy.